Multiple interneural communications of brachial plexus-anatomical description and clinical significance - K, Jasbir; G, Shivi; M, Vandana; KS, Rajesh; R, Gayatri (Faculty of Medicine, UKM Medical Centre, 2016)
Brachial plexus blockade requires efficient and thorough understanding of the detailed anatomy of the plexus and the variations associated with the plexus. Anomalies associated with the branches of the plexus may complicate attempts of nerve blockade for anesthesia. The present study reports a rare neural communication between ulnar and radial nerves, observed in the left axilla at high humeral level, 6cm distal to tip of coracoid process of scapula and 2.8cm proximal to the entry of the radial nerve into the radial groove. The communicating ramus also gave a branch to the medial head of triceps brachii. Musculocutaneous and median nerve connection was also observed in the arm, 9cm distal to the tip of coracoid process. The studies regarding the communication between ulnar and radial nerve are rare and the coexistence of this variation along with median and musculocutaneous nerve communication is unique. Knowledge of such rare variations and anomalies are important to minimize the possible complications of regional anesthesia and surgery. The present report is a humble attempt to reinforce awareness of such neural variations among clinicians.